Enhancing Pre-Service Teachers’ Literacy and Numeracy through Deep Learning Pedagogy: Evidence from a Quasi-Experimental Study - Arifin Ahmad; Moh. Nurhadi; Dahlia Rineva Puspitasari (International Journal of Educational Narratives, 2026)
Background. Literacy and numeracy are fundamental epistemic competencies required for professional teachers to analyze educational data and make evidence-based decisions. Despite their importance, many teacher education programs still rely on conventional instructional methods that promote surface learning rather than deep conceptual understanding. Purpose. This study examined the effectiveness of deep learning pedagogy in enhancing the literacy and numeracy competencies of pre-service teachers in the Teacher Professional Education (PPG) program. It further sought to identify the impact of this approach on students' analytical and reflective capacities compared to conventional methods. Method. A quantitative quasi-experimental design with a nonequivalent control group was employed. Participants were divided into an experimental group (deep learning pedagogy) and a control group (conventional methods). Data were gathered through pre-tests and post-tests and analyzed using independent sample t-tests and N-Gain analysis. Results. Baseline scores showed no significant differences between groups (p > 0.05). Post-intervention, the experimental group’s mean score rose to 87.50 (a 34.62% increase), significantly outperforming the control group’s 75.00 (a 15.38% increase). The t-test confirmed a significant difference (t = 3.678, p = 0.001, d = 0.92). Furthermore, N-Gain analysis revealed moderate improvement for the experimental group (g = 0.64) versus low improvement for the control group (g = 0.29). Conclusion. Deep learning pedagogy significantly enhances literacy and numeracy competencies within the Indonesian PPG context. Theoretically, these findings extend Fullan’s framework to professional teacher education. Practically, the study provides a replicable model for institutions aiming to foster data-informed teaching and metacognitive reflection among future educators.